2015
DOI: 10.1111/exd.12687
|View full text |Cite
|
Sign up to set email alerts
|

Mast cells are required for phototolerance induction and scratching abatement

Abstract: Dermal mast cells protect the skin from inflammatory effects of ultraviolet (UV) radiation and are required for UV-induced immune suppression. We sought to determine a potential mechanistic role of mast cells in reducing the sensitivity to UV radiation (i.e. phototolerance induction) through photohardening. We administered single UV exposures as well as a chronic UV irradiation regime to mast cell-deficient Kit(W-Sh/W-Sh) mice and their controls. The chronic irradiation protocol was similar to that given for p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 60 publications
(62 reference statements)
0
23
0
Order By: Relevance
“…More recently, Schweintzger et al . have shown that mast cells were required for inducing phototolerance and abating UVB‐induced scratching of the skin. Mast cell‐deficient mice (Kit W‐Sh/W‐Sh ) were prone to develop photo‐itch and more skin oedema and epidermal hyperplasia upon UVB exposure, and the implications of these findings were discussed in a commentary by De Gruijl in the context of increased scratching observed in carcinogenesis studies in mice after chronic (UVA‐1) irradiation .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…More recently, Schweintzger et al . have shown that mast cells were required for inducing phototolerance and abating UVB‐induced scratching of the skin. Mast cell‐deficient mice (Kit W‐Sh/W‐Sh ) were prone to develop photo‐itch and more skin oedema and epidermal hyperplasia upon UVB exposure, and the implications of these findings were discussed in a commentary by De Gruijl in the context of increased scratching observed in carcinogenesis studies in mice after chronic (UVA‐1) irradiation .…”
Section: Discussionmentioning
confidence: 99%
“…Despite these limitations, previous studies have shown that a lack of mast cells in mast cell‐deficient mice was the primary reason for the immunological alterations related to UVB exposure . However, before making any definite conclusions on the role of mast cells in PUVA‐induced immune suppression, experiments involving mast cell reconstitution or using newer models of mast cell deficiency are definitely needed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MCs have been suggested to play a role in PLE, and their number in the papillary dermis is increased after photohardening with PUVA . Along with this, MC‐ deficiency is associated with UV‐provoked itching . Including the data on MCs and UV tolerance (see below), it is possible that MC dysfunction is important in the development of PLE .…”
Section: The Role Of Mast Cells In Uv‐driven Diseasesmentioning
confidence: 99%
“…Schweintzger et al used mice homozygous for a different allele of Kit, Kit W‐Sh , to investigate the role of mast cells in inducing tolerance to UV‐mediated dermal hyperplasia and oedema. They found that deficiency of mast cells not only increased hyperplasia and oedema but also induced excessive scratching, a phenomenon that could be alleviated by grafting bone marrow‐derived cultured mast cells .…”
mentioning
confidence: 99%